Construction, stability and immunogenicity of recombinant BCG expressing HIV-1 subtype C gag under the control of MtrA promoter, with or without the leader sequences - Lebeko, Maribanyana R (Division of Virology, 2014)
This study aimed to compare recombinant mycobacteria expressing HIV-1 gag under the control of different promoters and leader sequences. This was done to determine whether the genetic stability of the recombinant mycobacteria could be improved by modification of these vector features and to gain insight into what types of immune responses may be elicited in mice.